5-HT2A Receptors in the Central Nervous System (The Receptors,, 2018)
5-HT2A receptors are G-protein coupled receptors that are widely distributed throughout the brain, most notably on neuronal and glial cells. 5-HT2A receptors have been implicated in various central physiological functions including mood regulation, memory, sleep, nociception, eating, and reward behaviors, and they are also believed to control the cardiovascular system. This book provides a comprehensive overview of these receptors including sections on their properties and distribution, approaches for their study, their role in a number of brain functions and diseases, and their role as therapeutic targets.